Communication Among Harvesters Leads to Sustainable Fishing Behaviour in a Continuous Time Common Pool Resource Experiment - Owusu, Kwabena A.; Kulesz, Micaela M.; Merico, Agostino (Frontiers in Marine Science, 2021)
The sustainable use of common pool resources (CPRs) such as fisheries constitutes a major challenge for society. A large body of empirical studies conducted in discrete time indicates that resource users are able to prevent the ‘tragedy of the commons' under institutional arrangements that can promote cooperation. However, the variability exhibited by the human behaviour and the dynamic nature of renewable resources require continuous time experiments to fully explain the mechanisms underpinning the sustainable use of resources. We conducted CPR experiments in continuous time to investigate how the extraction behaviour of resource users changes in real-time in response to changes in resource availability under communication and no communication. We find that when communication is allowed, users adjust their extraction efforts based on knowledge of previous resource availability. In contrast, when communication is not allowed, users do not incorporate resource availability into their utility function. These results suggest that communication does not merely provide a forum for coordination but mediates a causal relationship between resource levels and extraction behaviour. Our findings may help the development of effective resource management policies.